2021
DOI: 10.1038/s41598-021-86054-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of differentially culturable tubercle bacteria in sputum using mycobacterial culture filtrates

Abstract: Rapid detection of tuberculosis (TB) infection is paramount to curb further transmission. The gold standard for this remains mycobacterial culture, however emerging evidence confirms the presence of differentially culturable tubercle bacteria (DCTB) in clinical specimens. These bacteria do not grow under standard culture conditions and require the presence of culture filtrate (CF), from axenic cultures of Mycobacterium tuberculosis (Mtb), to emerge. It has been hypothesized that molecules such as resuscitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…When the MPN method was included in the analysis, it gave further support to the MBL assay detecting a population of bacteria that were still viable rather than residual rRNA from non-viable organisms. In vitro studies have begun to characterise these populations [34][35][36]. Our data further support the existence of these populations in mouse lungs.…”
Section: Discussionsupporting
confidence: 75%
“…When the MPN method was included in the analysis, it gave further support to the MBL assay detecting a population of bacteria that were still viable rather than residual rRNA from non-viable organisms. In vitro studies have begun to characterise these populations [34][35][36]. Our data further support the existence of these populations in mouse lungs.…”
Section: Discussionsupporting
confidence: 75%
“…The latter effect was alleviated in sputa from the cohort with DS TB after initiation of drug treatment, suggesting that the prior drug exposure experienced by subjects with DR TB may have contributed to this difference. What components of CF exert these effects and by what mechanisms remain unknown ( 12 ), making it difficult to draw biologic inferences. As a practical matter, it is advisable to perform MPN-LD assays both with and without CF to maximize detection of DD- Mtb .…”
Section: Discussionmentioning
confidence: 99%
“…This approach is often supplemented or replaced by assessing time to positivity (TTP) of sputum samples in an automated liquid culture system that measures the rate of depletion of oxygen from culture medium as a proxy for M. tuberculosis growth and quantity. These techniques may miss subpopulations of M. tuberculosis that are incapable of growing on solid medium or in liquid medium if the suspension has not been extensively diluted ( 3 12 ). These bacteria have been called by the interchangeable terms “viable but nonculturable” (VBNC- Mtb ) ( 13 ), “differentially culturable” (DCTB) ( 10 ), and “differentially detectable” M. tuberculosis (DD- Mtb ) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between biofilm formation and Rpfs in M. smegmatis has been recently demonstrated by Ealand et al [ 35 ]; they observed that simultaneous deletion of rpf genes hampered the development of biofilms and reduced drug tolerance, and that these effects were accompanied by a decrease in muropeptide production and altered peptidoglycan cross-linking. Recently, the same group has examined the role of M. tuberculosis Rpfs in reactivation processes by expressing them in M. smegmatis [ 36 ]. Their results indicate that the growth stimulatory effect observed with the culture filtrate is most likely the result of a combination of Rpfs with other factors [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the same group has examined the role of M. tuberculosis Rpfs in reactivation processes by expressing them in M. smegmatis [ 36 ]. Their results indicate that the growth stimulatory effect observed with the culture filtrate is most likely the result of a combination of Rpfs with other factors [ 36 ]. In our study, the changes in RpfE2 expression had a dramatic effect on M. smegmatis entering into the ‘non-culturable’ state but did not affect its reactivation from dormancy.…”
Section: Discussionmentioning
confidence: 99%